الرحلة في الرواية العربية المعاصرة : نماذج من الألفية الثالثة - هشام خوايجية (My University, 2024)
summary: The current research aims to find out the interaction between the journey and the contemporary Arabic novel, during the third millennium. The study included a theoretical and an applied aspect, where the study methodology was descriptive, and this is in view of the importance of the topic and its characteristics. The memorandum was titled The Journey in the Contemporary Arabic Novel, Models from the Third Millennium, as this topic has recently aroused passion among novelists. It carries with it problems that have raised questions about recalling history and documenting it narratively. I reached several results through these studies. We highlight their importance at the level of the travel text, which was represented in the title, which served as a significant icon as it formed a bridge to cross into an ancient history. We also find the spatial and temporal structure of the novel through narrative techniques, and this is to reveal the transformations taking place. Between the characters and their interaction, this novel is full of purposes, and there is a lot to explore the secrets of the topic. --------------- الملخص : يهدف البحث الحالي إلى معرفة التداخل بين الرحلة و الرواية العربية المعاصرة , خلال الألفية الثالثة. اشتملت الدراسة على جانب نظري و أخر تطبيقي , حيث جاء منهج الدراسة وصفيا , وهذا نظرا لأهمية الموضوع و خصائصه. جاءت المذكرة موسومة بالرحلة في الرواية العربية المعاصرة نماذج من الألفية الثالثة , حيث أثار هذا الموضوع الشغف إلى الروائيين حديثا , تحمل في طياتها من إشكاليات أثارت تساؤلات في استدعاء التاريخ و توثيقه روائيا. توصلت إلى نتائج عدة من خلال هذه الدراسات , نبرز أهميتها على مستوى النص ألرحلي و التي تمثلت في العنوان الذي جاء بمثابة أيقونة دالة حيث شكل جسرا للعبور إلى تاريخ عريق , نجد أيضا البناء المكاني و الزماني للرواية من خلال تقنيات السرد و هذا للكشف عن التحولات الحاصلة بين الشخصيات و تفاعلها , عما تزخر هذه الرواية بالمقاصد , و هناك الكثير في تصفح خبايا الموضوع . --------------------- Résumé : La recherche actuelle vise à découvrir l'interaction entre le voyage et le roman arabe contemporain, au cours du troisième millénaire. L'étude comprenait un aspect théorique et un aspect appliqué, où la méthodologie d'étude était descriptive, compte tenu de l'importance du sujet et de ses caractéristiques. Le mémorandum était intitulé Le voyage dans le roman arabe contemporain, modèles du troisième millénaire, car ce sujet a récemment suscité la passion des romanciers et pose des problèmes qui ont soulevé des questions sur la remémoration de l'histoire et sa documentation narrative. Grâce à ces études, j'ai obtenu plusieurs résultats. Nous soulignons leur importance au niveau du texte de voyage, qui était représenté dans le titre, qui servait d'icône significative car il formait un pont pour traverser une histoire ancienne. Nous retrouvons également le spatial. et la structure temporelle du roman à travers des techniques narratives, et ceci pour révéler les transformations qui s'opèrent entre les personnages et leur interaction, ce roman est plein d'objectifs, et il y a beaucoup à explorer les secrets du sujet.
Keywords: The Journey; the Contemporary Arabic Novel; Druze; Belgrade; Hannah Yacoub.; الرحلة; الرواية العربية المعاصرة; الدروز; بلغراد; حنة يعقوب.; Le Voyage; le roman arabe contemporain